2014
DOI: 10.1177/1048371314563828
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Enjoyment in the General Music Classroom

Abstract: Enjoyment is an important but often overlooked element in the music classroom. In this article, we review research literature related to enjoyment in musical interactions and discuss the role of enjoyment in the general music classroom. Drawing on research literature, our experience as general music teachers, and our research on enjoyment during musical play, we make recommendations for teachers interested in enhancing enjoyment in their classrooms. We include a teacher reflection template and an enjoyable ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Enjoyment is one goal some parents have for their children’s musical involvement (Youm, 2013). As parents and teachers consider how to socialize children for enjoyment, sensitivity to the balance points discussed previously is needed (Berger & Cooper, 2003; Custodero, 2002; Koops, 2012a; Koops & Keppen, 2015). Too much control on the part of adults, whether teachers or parents, may lead to a decrease in learner agency as well as lessened musical enjoyment (Berger & Cooper, 2003; Koops, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enjoyment is one goal some parents have for their children’s musical involvement (Youm, 2013). As parents and teachers consider how to socialize children for enjoyment, sensitivity to the balance points discussed previously is needed (Berger & Cooper, 2003; Custodero, 2002; Koops, 2012a; Koops & Keppen, 2015). Too much control on the part of adults, whether teachers or parents, may lead to a decrease in learner agency as well as lessened musical enjoyment (Berger & Cooper, 2003; Koops, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Implications for practitioners include increasing teacher awareness of which activities, elements, or conditions are enjoyable to students (for suggested tools for teachers to use in exploring these questions, see Koops & Keppen, 2015). By noting these textural and structural elements of enjoyment in one’s own music education setting, which could range from a private lesson studio to an elementary general classroom to a high school wind ensemble, educators have the information needed to work toward establishing an environment and activities that foster enjoyment in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Juntunen [5] concurred that children should be given opportunities to explore different ways to move and vary their movements in response to music. Noteworthy, Koops and Kuebel [6] argued that children's enjoyment is key to quality music learning. In their view, it is essential to analyze whether children enjoy the musical activities implemented in classrooms and observe how children express their enjoyment.…”
Section: Perspectives and Practices On Ece Music Education Around The...mentioning
confidence: 99%
“…Schei and Ødegaard [13] documented the case of ECE teachers in Norway conducting a childcentered music exploration theme-based activity, in which children created a story and improvised movements in response to music to express themselves. Koops and Kuebel [6] found that preschool teachers in the United States usually provide children with freedom of choice. For example, teachers allowed children to decide whether they participate in movement or vocal activities by choosing a dice representing the activity.…”
Section: Perspectives and Practices On Ece Music Education Around The...mentioning
confidence: 99%
See 1 more Smart Citation